Lectin Receptor-Like Kinases: The Sensor and Mediator at the Plant Cell Surface - Sun, Yali; Qiao, Zhenzhen; Muchero, Wellington; Chen, Jin-Gui (Frontiers in Plant Science, 2020)
Lectin receptor-like kinases (LecRLK), a plant-specific receptor-like kinase (RLK) sub-family, have been recently found to play crucial roles in plant development and responses to abiotic and biotic stresses. In this review, we first describe the classification and structures of Lectin RLKs. Then we focus on the analysis of functions of LecRLKs in various biological processes and discuss the status of LecRLKs from the ligands they recognize, substrate they target, signaling pathways they are involved in, to the overall regulation of growth-defense tradeoffs. LecRLKs and the signaling components they interact with constitute recognition and protection systems at the plant cell surface contributing to the detection of environmental changes monitoring plant fitness.